MANAGEMENT FEATURES OF SALES DEPARTMENT IN THE AUTOMOTIVE BUSINESS - S. Gusev (Вестник университета, 2016)
This article explores the highlights of the management of the sales Department, a dedicated psycho-emotional features of staff.